Temperature resistant sol-gels

By developing a crosslinked siloxane sol-gel containing specific organosilanes, hydrophobic agents and corrosion inhibitors, the problem of sol-gels prone to fading and cracking at high temperatures in the prior art is solved, corrosion resistance and aesthetics at high temperatures are achieved, and cost and environmental risks are reduced.

CN119614077APending Publication Date: 2025-03-14THE BOEING CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411261818.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-07
Filing Date
2024-09-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing sol-gel films used in aerospace applications are prone to fading and cracking at high temperatures, and contain harmful substances such as hexavalent chromium, which is difficult to meet the requirements of corrosion resistance and environmental protection.

Method used

A sol-gel mixture containing a first and second organosilane, a hydrophobic agent and a corrosion inhibitor of a specific structure was developed to form a crosslinked siloxane sol-gel by mixing and heating in an organic solvent.

Benefits of technology

The sol-gel remains transparent, non-cracking and fading at temperatures up to 450°F, and is free of chromate, reducing production and maintenance costs and extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614077A_ABST
    Figure CN119614077A_ABST
Patent Text Reader

Abstract

The present disclosure provides a sol-gel, and the present disclosure provides a crosslinked siloxane sol-gel. The sol-gel includes a first siloxane unit represented by formula (I): # imgabs0 # wherein X is oxygen, R1 is hydrogen, oxygen, a hydroxyl group or a silane group, R2 is hydrogen, a hydroxyl group or a silane group, each of R3 and R4 is independently a linear or branched C1-20 alkyl group, C1-20 cycloalkyl group, oxysilane group, ether, epoxide, arylalkyl fluoride group, cycloalkyl fluoride group, and aryl fluoride group, and n is 1 to 100. The sol-gel includes a second siloxane unit represented by formula (I), wherein the second siloxane unit is different from the first siloxane unit. The sol-gel includes a hydrophobing agent represented by formula (I), wherein the hydrophobing agent includes at least one alkyl fluoride group.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application Serial No. 63 / 582,213 filed on September 12, 2023, the contents of which are incorporated herein by reference. Technical Field

[0003] Various aspects of the present disclosure generally relate to corrosion resistant sol-gel films for aerospace applications. Background Art

[0004] Metals used in the manufacture of aircraft, spacecraft, and other machinery, such as steel, aluminum, aluminum alloys, and galvanized metals, are susceptible to corrosion. Typically, an anodic coating of a metal substrate, such as a sol-gel film, which has a corrosion inhibitor and a metal oxide processed throughout the sol-gel film, is placed on the metal substrate to reduce corrosion of the metal substrate. Chromates, such as hexavalent chromium zinc salts, are used as corrosion inhibitors in conjunction with the sol-gel film to help reduce corrosion of the metal substrate. However, there is regulatory pressure to eliminate the use of hexavalent chromium and other chromates from conversion coatings, primers, and manufacturing processes.

[0005] There is a need in the art for improved sol-gel films. Summary of the invention

[0006] In one aspect, the present disclosure provides a sol-gel mixture. The sol-gel mixture includes a first organosilane having a structure represented by Formula V:

[0007] Among them: Each R 10 , R 11 and R 12 Independently linear or branched C 1-20 Alkyl, and R 9 The sol-gel mixture includes a second organosilane represented by formula (IV), wherein the second organosilane is different from the first organosilane. The sol-gel mixture includes a hydrophobic agent in an amount of about 1 wt % to about 8 wt % of the total amount of the sol-gel mixture.

[0008] In another aspect, the present disclosure provides a cross-linked siloxane sol-gel. The sol-gel comprises a first siloxane unit represented by formula (I): Where X is oxygen, R 1 is hydrogen, oxygen, hydroxyl or silane group, R 2 is a hydrogen, hydroxyl or silane group, each R 3 and R 4 Independently linear or branched C 1-20Alkyl, C 1-20 Cycloalkyl, oxysilane, ether, epoxide, arylalkyl fluoride, cycloalkyl fluoride and aryl fluoride groups, and n is 1 to 100. The sol-gel includes a second siloxane unit represented by formula (I), wherein the second siloxane unit is different from the first siloxane unit. The sol-gel includes a hydrophobic agent represented by formula (I), wherein the hydrophobic agent includes at least one alkyl fluoride group.

[0009] In another aspect, the present disclosure provides a method for preparing a sol-gel from a sol-gel mixture. The method includes preparing a sol-gel mixture by mixing a first organosilane and a second organosilane in an organic solvent. A hydrophobic agent is added to the sol-gel mixture. The sol-gel mixture is cured to form a sol-gel. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order that the manner in which the above-described features may be understood in detail, a more particular description, briefly summarized above, may be had by reference to aspects of embodiments, some of which are illustrated in the accompanying drawings.

[0011] Figure 1 is a side view of a corrosion-inhibiting sol-gel disposed on a substrate in accordance with various aspects of the present disclosure.

[0012] Figure 2 is a schematic diagram of a method for preparing a sol-gel according to various aspects of the present disclosure.

[0013] Figure 3A and Figure 3B The water contact angles of the sol-gel before heating the sol-gel at 250° C. for 100 hours and after heating the sol-gel at 250° C. for 100 hours according to various aspects of the present disclosure are presented. Figure 3A Water contact angles are shown before heating the sol-gel at 250 °C for 100 h. Figure 3B Shown are the water contact angles after heating the sol-gel at 250 °C for 100 h.

[0014] FIG. 4A to FIG. 4D Optical images of a sol-gel using a microscope or scanning electron microscopy (SEM) technique before and after heating the sol-gel at 250° C. for 100 hours according to various aspects of the present disclosure are shown. Figure 4A Microscope images of the sol-gel before heating at 250 °C for 100 h are shown. Figure 4B Microscope images of a sol-gel after heating at 250 °C for 100 h are shown. Figure 4C Shown is a SEM image of the sol-gel before heating at 250 °C for 100 h. Figure 4DShown are SEM images of the sol-gel after heating at 250 °C for 100 h.

[0015] Figure 5 An infrared image of the first mixture from a Fourier transform infrared spectrometer is shown.

[0016] Figure 6 A thermogravimetric analysis of the first mixture is shown.

[0017] FIG. 7A to FIG. 7C Optical images of sol-gels using SEM techniques after heating sol-gels having different molar ratios of first and second organosilanes at 250° C. for 100 hours according to various aspects of the present disclosure are shown. Fig. 7A SEM images of a sol-gel having a molar ratio of the first organosilane to the second organosilane of 2:1 after heating the sol-gel at 250°C for 100 hours are shown. Figure 7B SEM images of a sol-gel having a molar ratio of the first organosilane to the second organosilane of 3:1 after heating the sol-gel at 250° C. for 100 hours are shown. Figure 7C SEM images of a sol-gel having a molar ratio of the first organosilane to the second organosilane of 4:1 after heating the sol-gel at 250° C. for 100 hours are shown.

[0018] Figure 8 Polarization plots of the second mixture before heating the sol-gel at 250° C. for 100 hours and after heating the sol-gel at 250° C. for 100 hours are shown in accordance with various aspects of the present disclosure.

[0019] Fig. 9 is an infrared image of the second mixture from a Fourier transform infrared spectrometer.

[0020] Fig. 10A and Fig. 10B The water contact angles of the sol-gel before heating the sol-gel at 250° C. for 100 hours and after heating the sol-gel at 250° C. for 100 hours according to various aspects of the present disclosure are presented. Fig. 10A Water contact angles are shown before heating the sol-gel at 250 °C for 100 h. Fig. 10B Shown is the water contact angle after heating the sol-gel at 250°C for 100 hours.

[0021] Fig.11 Polarization plots of the second mixture before heating the sol-gel at 250° C. for 100 hours and after heating the sol-gel at 250° C. for 100 hours are shown, according to various aspects of the present disclosure.

[0022] Fig. 12A and Fig. 12BOptical images of a sol-gel using SEM techniques before heating the sol-gel at 250° C. for 100 hours and after heating the sol-gel at 250° C. for 100 hours in accordance with various aspects of the present disclosure are shown. Fig. 12A Shown is a SEM image of the sol-gel before heating at 250 °C for 100 h. Fig. 12B Shown are SEM images of the sol-gel after heating at 250 °C for 100 h.

[0023] Fig.13A and Fig. 13B The water contact angles of a sol-gel having a hydrophobic agent before heating the sol-gel at 250° C. for 100 hours and after heating the sol-gel at 250° C. for 100 hours according to various aspects of the present disclosure are shown. Fig.13A Shown are the water contact angles before heating the sol-gel at 250°C for 100 hours. Fig. 13B Shown are the water contact angles after heating the sol-gel at 250°C for 100 hours.

[0024] Fig.14 Polarization plots of a sol-gel with a hydrophobic agent before heating the sol-gel at 250° C. for 100 hours and after heating the sol-gel at 250° C. for 100 hours are shown in accordance with various aspects of the present disclosure.

[0025] Fig.15 An infrared image of the second mixture with the hydrophobic agent from a Fourier transform infrared spectrometer is shown.

[0026] Fig.16 An infrared image of the second mixture with the hydrophobic agent and the crosslinking agent from a Fourier transform infrared spectrometer is shown. DETAILED DESCRIPTION

[0027] The present disclosure provides compositions and methods for producing sol-gels. In general, the sol-gels described herein can withstand temperatures up to 450°F while maintaining corrosion resistance because the hydrophobicity of the sol-gel remains stable at high temperatures. In fact, the hydrophobicity can increase after exposure to temperatures up to 450°F, thereby improving water resistance and corrosion resistance while maintaining structural properties, such as strength. At high temperatures, the sol-gel coating can remain transparent with little to no cracking or fading.

[0028] The sol-gel of the present disclosure is substantially homogeneous, with only limited and / or no metal oxides, which can reduce cracking and fading of the sol-gel while maintaining hydrophobicity to extend the life of the sol-gel. When the sol-gel of the present disclosure is applied to a metal and / or alloy substrate, it can prevent fading and reduced corrosion resistance when operated at temperatures up to 450°F (232°C) and then cooled from the high temperature. The reason for preventing fading and increasing corrosion resistance can be the increase in hydrophobicity, which allows reduced water penetration, which reduces fading because light is not reflected along the cracks formed. In addition, compared with traditional sol-gels, the sol-gel of the present disclosure reduces fading, thereby maintaining the aesthetics of the sol-gel. The sol-gel of the present disclosure can enhance the structural integrity, hydrophobicity and corrosion resistance of the film after operation at high temperatures, such as up to 450°F.

[0029] In addition, since metal oxides increase the strength of the sol-gel, thereby limiting the repair ability, the presence of limited and / or no metal oxides in the sol-gel can make the application, maintenance and repair of the sol-gel easier. Therefore, the sol-gel of the present disclosure allows for improved repair ability, thereby reducing the maintenance and repair costs of the sol-gel coating because there are limited or no metal oxides therein. The sol-gel described herein may be chromate-free. Optionally, the sol-gel described herein is chromate-free. The sol-gel described herein can involve only a single-tank system, unlike traditional sol-gel coatings, which require a two-component system to form the sol-gel (with a corrosion inhibitor). The reduction and / or elimination of chromates and two-component systems reduces costs, maintenance and application challenges.

[0030] Metal substrate

[0031] The metal substrate includes a metal aircraft surface, which may include steel or an alloy with a major component such as aluminum. The metal substrate may include a major component and a minor component, called an intermetallic compound. For example, the intermetallic compound may include copper, a metal that is easily corroded. The metal substrate may include an aluminum substrate. The metal substrate may include an aluminum substrate with a copper intermetallic compound. As a non-limiting example, the metal substrate may be a 2024 aluminum substrate, a 7075-T6 aluminum substrate, or a 7178 aluminum substrate.

[0032] Sol-Gel

[0033] The term "sol-gel" is an abbreviation for solution-gelation and refers to a series of reactions in which a soluble organic ligand, typically an organosilane, is hydrolyzed to form an organosilane hydroxide. The organic ligand is tailored to correspond to the binding structure of the resin. An inorganic acid, such as an acyl halide, e.g., hydrochloric acid, hydrobromic acid, thionyl chloride, propionyl chloride, or benzoyl chloride, is added to the organosilane hydroxide to form a water-based or alcohol-based system, e.g., an ethanol system. Depending on the reaction conditions, the organosilane polymer can condense or grow to form a silica network gel. The ratio of organic to inorganic in the polymer matrix can be controlled to suit the performance requirements of a specific application.

[0034] The sol-gel of the present disclosure includes a plurality of siloxane units represented by formula (I):

[0035]

[0036] Where X is oxygen, R 1 is hydrogen, oxygen, hydroxyl or silane group, R 2 is a hydrogen, hydroxyl or silane group, each R 3 and R 4 Independently linear or branched C 1-20 Alkyl, C 1-20 Cycloalkyl, silane, ether, epoxide, arylalkyl fluoride, cycloalkyl fluoride and aryl fluoride groups, and n is 1 to 100. Alkyl includes linear or branched C 1-20 Alkyl. C 1-20 Alkyl includes methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl and eicosyl. Ether includes polyethylene glycol ether, polypropylene glycol ether, C1-C 20 Alkyl ethers, aryl ethers and cycloalkyl ethers. Alkyl fluorides include straight-chain or branched C 1-20 For example, the sol-gel of the present disclosure may include two or more independent siloxane units represented by formula (II):

[0037]

[0038] Where X 1 and X 2 is oxygen, R 1 is hydrogen, oxygen, hydroxyl or silane group, R 2 is a hydrogen, hydroxyl or silane group, each R 3 , R 4 , R 5 and R 6Independently linear or branched C 1-20 Alkyl, C 1-20 Cycloalkyl, oxysilane, ether, epoxide, arylalkyl fluoride, cycloalkyl fluoride and aryl fluoride groups, n is 1 to 100, m is 1 to 100.

[0039] For example, the sol-gel of the present disclosure may include three or more independent siloxane units represented by formula (III):

[0040]

[0041] Where X 1 , X 2 and X 3 is oxygen, R 1 is hydrogen, oxygen, hydroxyl or silane group, R 2 is a hydrogen, hydroxyl or silane group, each R 3 , R 4 , R 5 , R 6 , R 7 and R 8 Independently linear or branched C 1-20 Alkyl, C 1-20 Cycloalkyl, oxysilane, ether, epoxide, arylalkyl fluoride, cycloalkyl fluoride and aryl fluoride groups, n is 1 to 100, m is 1 to 100, and p is 1 to 100. For example, X 1 and X 2 is oxygen, R 1 is hydroxyl, R 2 is silane, R 3 , R 4 , R 5 and R 7 is oxygen silane, R 6 is an alkene, R 7 is oxygen silane, R 8 is a C9 alkyl fluoride, n is 1 to 100, m is 1 to 100, and p is 1 to 100.

[0042] The siloxane units may be polymerized to form a polymeric siloxane. The polymeric siloxane includes a first siloxane unit represented by Formula III wherein R 3 , R 4 , R 5 , R 6 , R 7 or R 8 R crosslinked to the second siloxane unit represented by Formula III 3 , R 4 , R 5 , R 6 , R 7 or R 8For example, R of the first siloxane unit 5 The second R of the second siloxane unit may 5 The crosslinking or reaction forms a polymeric siloxane having a first siloxane unit and a second siloxane unit covalently bonded. The amount of crosslinking can vary based on the reactivity of the R group on each of the plurality of siloxane units. For example, the polymeric siloxane can be represented by formula (IV):

[0043]

[0044] Here, n is 1 to 100.

[0045] The sol-gel may have a thickness of about 1 μm to about 10 μm, such as about 1 μm, about 2 μm, about 3 μm, about 4 μm, about 5 μm, about 6 μm, about 7 μm, about 8 μm, or about 10 μm. The sol-gel may have a thickness of about 400 mg / ft 2 About 800mg / ft 2 Weight density, for example, about 400 mg / ft 2 , about 500mg / ft 2 , about 600mg / ft 2 , about 700mg / ft 2 2 or about 800 mg / ft 2 .

[0046] Organosilanes

[0047] The weight fraction (wt %) of the organosilane in the sol-gel is from about 0.1 wt % to about 70 wt %, such as from about 35 wt % to about 70 wt %, such as from about 45 wt % to about 65 wt %, such as from about 50 wt % to about 65 wt %, such as from about 55 wt % to about 60 wt % by volume of the total sol-gel coating.

[0048] The organosilane disclosed in the present invention is represented by formula (V):

[0049]

[0050] in:

[0051] Each R 10 , R 11 and R 12 is independently a linear or branched C 1-20 Alkyl. C 1-20 Alkyl includes methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, and eicosyl;

[0052] R 9 is selected from alkyl, cycloalkyl, ether, epoxide and aryl. Alkyl includes straight chain or branched C 1-20 Alkyl. C 1-20 Alkyl includes methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl and eicosyl. Ether includes polyethylene glycol ether, polypropylene glycol ether, C1-C 20 Alkyl ethers, aryl ethers and cycloalkyl ethers.

[0053] The ether is selected from:

[0054]

[0055]

[0056] Wherein n is a positive integer. In at least one aspect, n is a positive integer, and the number average molecular weight (Mn) of the ether is from about 300 to about 500, such as from about 375 to about 450, such as from about 400 to about 425.

[0057] The organosilane is represented by Compound 1, Compound 2 or Compound 3:

[0058]

[0059] The organosilane is selected from 3-aminopropyltriethoxysilane, p-aminophenyltrimethoxysilane, p-aminophenyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, n-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, n-anilinopropyltrimethoxysilane, ethyl Alkenylmethyldiethoxysilane, vinyltriethoxysilane, methyltrimethoxysilane, tetraethylorthosilicate, vinyltrimethoxysilane, bis(trimethoxysilyl)ethane, bis(trimethoxysilyl)ethane, bis[3-(trimethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]disulfide, bis[3-(trimethoxysilyl)propyl]disulfide, bis[3-(triethoxysilyl)propyl]trisulfide, bis[3-(triethoxysilyl)propyl]trisulfide, bis[3-(triethoxysilyl)propyl]tetrasulfide and bis[3-(trimethoxysilyl)propyl]tetrasulfide.

[0060] One or more organosilanes are included to form the sol-gel of the present disclosure. At least a first organosilane and a second organosilane are included. For example, the first organosilane may include tetraethyl orthosilicate, and the second organosilane may include vinyl triethoxysilane. The concentration of the first organosilane in the sol-gel is from about 0.01 mol to about 1.0 mol, for example, from about 0.01 mol to about 5 mol, from about 0.1 mol to about 2 mol, from about 0.15 mol to about 1 mol, from about 0.1 mol to about 0.2 mol, such as about 0.15 mol. The concentration of the second organosilane in the sol-gel is from about 0.01 mol to about 1.0 mol, for example, from about 0.01 mol to about 5 mol, from about 0.1 mol to about 2 mol, from about 0.15 mol to about 1 mol, from about 0.1 mol to about 0.2 mol, such as about 0.15 mol. The ratio of the first organosilane to the second organosilane is about 0.1:1 to about 10:1, such as about 0.1:1 to about 5:1, about 0.5:1 to about 4:1, about 1:1 to about 3:1, about 1.5:1 to about 2.5:1, such as about 2:1. The organosilanes of the present disclosure provide sol-gels that can operate at temperatures up to 450°F without fading and / or cracking. Without being bound by theory, the ratio of the first organosilane to the second organosilane is about 1:1 to about 2:1, which can provide a sol-gel that can operate at temperatures up to 450°F due to the crosslinking between the first organosilane and the second organosilane. In addition, it is found that the ratio of about 1:1 to about 2:1 can prevent precipitation, be transparent with minimal haze, and improve heat resistance compared to the optional ratio of the organosilanes. Compared with traditional sol-gels, the organosilanes of the present disclosure also allow for an increase in the organic content in the sol-gel, making the deposited layer of the sol-gel thicker while reducing the possibility of cracking.

[0061] Acid Catalyst

[0062] The acid catalyst used to form the sol-gel of the present disclosure increases the hydrolysis reaction rate and reduces the pH of the sol-gel. The pH of the sol-gel (and the composition forming the sol-gel) can be controlled by using an acid catalyst. The acid catalyst of the present disclosure includes an inorganic acid, such as an acyl halide. Acyl halides include, for example, hydrochloric acid, hydrobromic acid, thionyl chloride, propionyl chloride or benzoyl chloride.

[0063] The pH of the sol-gel of the present disclosure is from about 2 to about 5, such as from about 3 to about 4. The concentration of the acid catalyst in the sol-gel is from about 0.01 mol to about 1.0 mol, such as from about 0.01 mol to about 5 mol, from about 0.1 mol to about 2 mol, from about 0.15 mol to about 1 mol, from about 0.1 mol to about 0.2 mol, such as about 0.15 mol. The ratio of the acid catalyst to the organosilane in the sol-gel can be from about 0.5:1 to about 2:1, such as from about 0.5:1 to about 1.5:1, from about 1:1 to about 1.5:1, or from about 0.8:1 to about 1.8:1. For example, the first organosilane in the sol-gel is about 0.1 mol, and the acid catalyst is about 0.1 mol. As a further example, the second organosilane in the sol-gel is about 0.05 mol, and the acid catalyst is about 0.1 mol.

[0064] Without being bound by theory, it is believed that these ratios of acid catalyst not only help increase the hydrolysis reaction rate, but also protonate the mercaptan portion of the corrosion inhibitor, which reduces or prevents the corrosion inhibitor from reacting with other components in the sol-gel.

[0065] Hydrophobic Agent

[0066] The hydrophobic agent used to form the sol-gel of the present disclosure provides hydrophobicity to the sol-gel, preventing water from penetrating into the sol-gel and contacting the metal substrate. The hydrophobic agent of the present disclosure is an organic or inorganic compound having one or more fluorine groups. Without being bound by theory, the fluorine groups serve to increase the hydrophobicity of the sol-gel because the arrangement of fluorine in the sol-gel produces a net zero dipole interaction and results in poor van der Waals interactions with water.

[0067] The hydrophobic agent of the present disclosure is an organic compound including a fluoride group. For example, the hydrophobic agent of the present disclosure is represented by the chemical formula Si(OR')3R*, wherein each R' is independently a linear or branched C 1-20 Alkyl. C 1-20 The alkyl group includes methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl and eicosyl, and R* is selected from alkyl fluoride, cycloalkyl fluoride and aryl fluoride groups. Alkyl fluoride includes a linear or branched C fluoride having at least one fluorine atom. 1-20 Alkyl. C 1-20 Alkyl includes methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl and eicosyl. For example, the hydrophobic agent may include perfluorooctyltriethoxysilane.

[0068] The weight fraction (wt%) of the hydrophobic agent in the total sol-gel by volume is from about 1 wt% to about 8 wt%, such as about 2 wt% to about 5 wt%, about 2 wt% to about 4 wt%, about 2 wt% to about 3 wt%, such as about 2 wt%. For example, the hydrophobic agent in the sol-gel can account for 2 wt% of the total sol-gel, the first organosilane accounts for about 33 wt%, and the second organosilane accounts for about 15 wt% by volume. The hydrophobic agent incorporated into the sol-gel increases the hydrophobicity of the sol-gel, increases the water contact angle, and reduces the penetration of water into the metal substrate. In addition, this can promote corrosion protection and maintain service life because when the sol-gel is heated to 450°F, cracks in the sol-gel are minimized or even eliminated.

[0069] Corrosion Inhibitor

[0070] The corrosion inhibitor used to form the sol-gel of the present disclosure can provide corrosion resistance (to water) to the metal substrate adjacent to the sol-gel. The corrosion inhibitor of the present disclosure is a compound having one or more thiol moieties. The metal aircraft surface may include steel or an alloy having a main component such as aluminum and a minor component called an intermetallic compound. For example, the intermetallic compound generally contains copper, a metal that is susceptible to corrosion. Without being bound by theory, it is believed that the interaction between the thiol moiety of the corrosion inhibitor of the present disclosure and the copper-containing intermetallic compound on the metal surface (such as the aluminum alloy surface) prevents corrosion of the metal surface. More specifically, the interaction between the thiol moiety of the corrosion inhibitor of the present disclosure and the intermetallic compound prevents the reduction of the intermetallic compound by slowing down the rate of redox and reducing the degree of oxidation of metal alloys such as aluminum alloys.

[0071] The corrosion inhibitor of the present disclosure is an organic compound that includes a disulfide group and / or a thiol acid salt group (e.g., a metal-sulfide bond). For example, the corrosion inhibitor is not an organometallic corrosion inhibitor. The corrosion inhibitor is of the formula: R 1 --S n --X--R 2 Indicates that R 1 is an organic group, n is an integer greater than or equal to 1, X is a sulfur atom or a metal atom, and R 2 is an organic group. 1 and R 2 One or both of the above may include additional polysulfide groups and / or thiol groups. In addition, the corrosion inhibitor includes a compound having the formula: 1 --S n --X--R 2 ) q - polymer, wherein R 1 is an organic group, n is a positive integer, X is a sulfur or metal atom, R2 is an organic group, q is a positive integer. (of polymeric or monomeric corrosion inhibitors) R 1 and R 2 R is independently selected from hydrogen, alkyl, cycloalkyl, aryl, thiol, polysulfide or thione. 1 and R 2 R may be independently substituted with a moiety selected from alkyl, amino, phosphorus-containing, ether, alkoxy, hydroxyl, sulfur-containing, selenium or tellurium. 1 and R 2 Each has 1 to 24 carbon atoms and / or non-hydrogen atoms. For example, R 1 and R 2 Examples of heterocyclic groups include azole, triazole, thiazole, dithiazole and / or thiadiazole.

[0072] The corrosion inhibitor includes a metal in a metal-thiol salt complex. The corrosion inhibitor may include a metal center and one or more thiol groups (ligands) that are bound and / or coordinated to the metal center in a metal-sulfide bond. Thiol salts are derivatives of thiols in which a metal atom replaces the hydrogen bound to the sulfur. The general formula of thiol salts is MS--R 1 , where M is metal and R 1 is an organic group. 1 A disulfide group may be included. The general formula of the metal-thiol salt complex is M-(S--R 1 ) n , wherein n is generally an integer from 2 to 9, and M is a metal atom. The metal includes copper, zinc, zirconium, aluminum, iron, cadmium, lead, mercury, silver, platinum, palladium, gold and / or cobalt.

[0073] Corrosion inhibitors include azole compounds. Examples of suitable azole compounds include cyclic compounds with 1 nitrogen atom, such as pyrrole, cyclic compounds with 2 or more nitrogen atoms, such as pyrazole, imidazole, triazole, tetrazole and pentaazole, cyclic compounds with 1 nitrogen atom and 1 oxygen atom, such as oxazole and isoxazole, and cyclic compounds with 1 nitrogen atom and 1 sulfur atom, such as thiazole and isothiazole. Non-limiting examples of suitable azole compounds include 2,5-dimercapto-1,3,4-thiadiazole, 1H-benzotriazole, 1H-1,2,3-triazole, 2-amino-5-mercapto-1,3,4-thiadiazole, also known as 5-amino-1,3,4-thiadiazole-2-thiol, 2-amino-1,3,4-thiadiazole. For example, but not limited to, the azole can be 2,5-dimercapto-1,3,4-thiadiazole. The azole may be present in the composition at a concentration of 0.01 g / L to 1 g / L of the sol-gel composition, such as 0.4 g / L of the sol-gel composition. The azole compound may include benzotriazole and / or 2,5-dimercapto-1,3,4-thiadiazole.

[0074] The corrosion inhibitors disclosed herein include heterocyclic thiols and amines, which can eliminate redox. Heterocyclic thiols include thiadiazoles having one or more thiol moieties. Non-limiting examples of thiadiazoles having one or more thiol moieties include 1,3,4-thiadiazole-2,5-dithiol and thiadiazoles represented by formula (VI) or formula (VII):

[0075]

[0076] The thiadiazoles of formula (VI) are commercially available from Vanderbilt Chemicals, LLC (Norwalk, Connecticut) under the name 829. The thiadiazole of formula (VII) is available from WPC Technologies, Inc. TM Purchased by Oak Creek, Wisconsin, as InhibiCor TM 1000.

[0077] The corrosion inhibitor of the present disclosure can be a derivative of 2,5-dimercapto-1,3,4-thiadiazole, symbolized as HS-CN2SC-SH or "DMTD", and selected derivatives of trithiocyanuric acid ("TMT") used as a coating corrosion inhibitor in relation to paints. Examples include 2,5-dimercapto-1,3,4-thiadiazole (DMTD) and 2,4-dimercapto-s-triazolo[4,3-b]-1,3-4-thiadiazole and trithiocyanuric acid (TMT). Other examples include N-, S- and N,N-, S,S- and N,S-substituted derivatives of DMTD, such as 5-mercapto-3-phenyl-1,3,4-thiadiazoline-2-thione or bismercapto II (3-phenyl-1,3,4-thiadiazolidine-2,5-dithione) and various S-substituted derivatives of trithiocyanuric acid. Other examples include 5,5′ dithio-bis(1,3,4-thiadiazole-2(3H)-thione or (DMTD)2, or (DMTD), polymers of DMTD; 5,5′ thio-bis(1,3,4-thiadiazole-2(3H)-thione; or (TMT)2, dimers and polymers of TMT. Other examples include the general formula: M(DMTD) nSalts of DMTD wherein n=1, 2 or 3 and M is a metal cation such as M=Zn(II), Bi(III), Co(II), Ni(II), Cd(II), Pb(II), Ag(I), Sb(III), Sn(II), Fe(II) or Cu(II) (e.g., ZnDMTD, Zn(DMTD)2, Bi(DMTD)3); similar salts of TMT, e.g., ZnTMT, in a 1:1 ratio; and, in addition, comparable soluble Li(I), Ca(II), Sr(II), Mg(II), La(III), Ce(III), Pr(III) or Zr(IV) salts. Additional examples include the general formula M[(DMTD) n ] m (DMTD) n Salts wherein n=2 or n>2, m=1, 2 or 3, and M is a metal cation, such as M=Zn(II), Bi(III), Co(II), Ni(II), Cd(II), Pb(II), Ag(I), Sb(III), Sn(II), Fe(II) or Cu(II). Typical examples are: Zn[(DMTD)2], Zn[(DMTD)2]2.

[0078] Additional examples include DMTD, (DMTD) n or 5,5′thio-bis(1,3,4-thiadiazole-2(3H)-thione or 2,4-dimercapto-s-triazolo-[4,3-b]-1,3-4-thiadiazole) ammonium, arylammonium or alkylammonium salts. Typical examples include: cyclohexylamine:DMTD in ratios of 1:1 and 2:1; dicyclohexylamine:DMTD in ratios of 1:1 and 2:1; aniline:DMTD in ratios of 1:1 and 2:1; similar salts of TMT, such as dicyclohexylamine:TMT in a ratio of 1:1. Other examples include DMTD or (DMTD) n And the polyammonium salt formed by TMT and polyamine.

[0079] Additional examples include intrinsically conductive polyaniline doped with DMTD or (DMTD)2 or 5,5′-thio-bis(1,3,4-thiadiazole-2(3H)-thione) and TMT; intrinsically conductive polypyrrole and / or polythiophene doped with DMTD, (DMTD)2 and 5,5′-thio-bis(1,3,4-thiadiazole-2(3H)-thione) and / or TMT.

[0080] Additional examples include micro- or nanocomposites of polyDMTD / polyaniline, polyDMTD / polypyrrole, and polyDMTD / polythiophene; with TMT; and similar micro- or nanocomposites with 5,5′-thio-bis(1,3,4-thiadiazole-2(3H)-thione; DMTD or salts of DMTD or derivatives of DMTD and TMT) as organic components of various pigment-grade inorganic matrices or physical mixtures. These inorganic matrices may include non-toxic anionic and cationic species with corrosion inhibition properties, such as MoO4 - PO4 - 、HPO3 - , polyphosphate, BO2 - 、SiO4 - 、NCN - WO4 - , phosphomolybdate, phosphotungstate and Mg, Ca, Sr, La, Ce, Zn, Fe, Al, Bi respectively.

[0081] Additional examples include DMTD or salts of DMTD or derivatives of DMTD and TMT in encapsulated form, for example, inclusion complexes in various polymer matrices, or in the form of cyclodextrin inclusion complexes or microcapsules.

[0082] The pigment-grade form of DMTD includes Zn(DMTD)2 and Zn-DMTD (other organic and inorganic salts of the former, etc.) with inorganic products or corrosion-inhibiting pigments, such as phosphates, molybdates, borates, silicates, tungstates, phosphotungstates, phosphomolybdates, cyanides or carbonates of the previously specified cationic species and oxides. Examples include zinc phosphate, cerium molybdate, calcium silicate, strontium borate, zinc cyanamide, cerium phosphotungstate, ZnO, CeO2, ZrO2 and amorphous SiO2.

[0083] The corrosion inhibitor is a lithium ion, and a counterion, which may include various ions known to form salts with lithium. Non-limiting examples of counterions suitable for forming salts with lithium include carbonate, hydroxide and silicate (e.g., orthosilicate and metasilicate). For example, the corrosion inhibitor includes a lithium carbonate salt, a lithium hydroxide salt or a lithium silicate salt (e.g., lithium orthosilicate or lithium metasilicate). Counterions include various ions known to form salts with other Group IA (or Group 1) metals (e.g., Na, K, Rb, Cs and / or Fr). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonate, hydroxide and silicate (e.g., orthosilicate and metasilicate). For example, the corrosion inhibitor includes an alkali carbonate, an alkali hydroxide salt and / or an alkali silicate (e.g., an alkali orthosilicate or an alkali metasilicate), but is not limited thereto. For example, some examples of suitable salts include carbonates, hydroxides, and silicates (such as orthosilicates or metasilicates) of sodium, potassium, rubidium, cesium, and francium.

[0084] The weight fraction (wt%) of the corrosion inhibitor in the total amount of the sol-gel is from about 1wt% to about 10wt%, such as from about 3wt% to about 10wt%, such as from about 1wt% to about 5wt%, such as from about 5wt% to about 10wt%, for example, about 1wt%, about 5wt% or about 10wt%. The corrosion inhibitor added to the sol-gel can provide an additional corrosion protection layer on the adjacent metal surface. When combined with the hydrophobicity of the sol-gel of the present disclosure, the water resistance and corrosion resistance are enhanced.

[0085] Topcoat

[0086] The topcoat of the present disclosure can be applied on the primer coating to form the sol-gel of the present disclosure so that the metal substrate adjacent to the sol-gel has corrosion resistance (to water). The topcoat can include an organic topcoat, such as a polymer coating (e.g., an epoxy coating and / or a polyurethane coating), a polymer material, a composite material (e.g., a filled composite material and / or a fiber-reinforced composite material), a laminate or a mixture thereof. The topcoat includes at least one or a combination of a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a paint, a polyurethane, and a polyester. For example, but not limited to this, the topcoat is a polyurethane. The polyurethane topcoat prevents water from penetrating the coating, thereby improving corrosion protection. The thickness of the topcoat can be about 2 mils to about 3 mils, such as about 2.1 mils to about 2.9 mils, such as about 2 mils, about 2.1 mils, about 2.2 mils, about 2.3 mils, about 2.4 mils, about 2.5 mils, about 2.6 mils, about 2.7 mils, about 2.8 mils, about 2.9 mils, about 3 mils. For example, but not limited to, the topcoat has a thickness of about 2 mils to about 3 mils, and the primer has a thickness of about 0.3 mils to about 2.5 mils.

[0087] Sol-Gel System

[0088] Figure 1 is a side view of a corrosion inhibiting sol-gel placed on a substrate. The corrosion inhibiting sol-gel system 100 includes a sol-gel 102 placed on a material substrate 104. In one embodiment, it is recognized that the sol-gel 102 has heat resistance due to the ratio of the first organosilane and the second organosilane, which provides heat resistance due to the cross-linking of the first organosilane and the second organosilane. In addition, it is found that a ratio of about 1:1 to about 2:1 can prevent precipitation, be transparent with minimal haze, and improve heat resistance compared to other organosilane ratios. Due to the hydrophobicity of the organosilane and the hydrophobic agent, the sol-gel 102 has corrosion inhibition properties and provides corrosion protection for the material substrate 104. The sol-gel 102 promotes adhesion between the metal substrate 104 and the second layer 106. The second layer 106 can be a sealant, an adhesive, a primer, or a coating, which can be deposited on the sol-gel 102 by, for example, spray drying.

[0089] The material substrate 104 may be any suitable material as described herein, and / or may include any suitable structure that benefits from the sol-gel 102 placed thereon. The material substrate 104 may be defined as one or more components (e.g., structural or mechanical components) of a device exposed to the environment, such as an aircraft, a watercraft, a spacecraft, a land vehicle, equipment, a civil structure, a fastening assembly, a wind turbine, and / or other equipment susceptible to environmental degradation. The material substrate 104 may be part of a larger structure, such as a vehicle component. A vehicle component refers to any suitable component of a vehicle, such as a structural component, such as a landing gear, a panel, or a joint of an aircraft. Examples of vehicle components include rotors, landing gear, auxiliary power units, aircraft noses, fuel tanks, tail cones, panels, coated lap joints between two or more panels, wing and fuselage assemblies, structural aircraft composites, fuselage body joints, rib and skin joints, and / or other internal components. The material substrate 104 can be made of at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, nickel, iron, iron alloy, steel, titanium, titanium alloy, copper, copper alloy, glass / silicon dioxide and other inorganic or mineral substrates. The material substrate 104 is made of steel. The material substrate 104 can be a "bare" substrate, with no electroplating (unplated metal), conversion coating and / or corrosion protection between the material substrate 104 and the sol-gel 102. In addition or alternatively, the material substrate 104 can also include surface oxidation and / or hydroxylation. Therefore, the sol-gel 102 can be directly bonded to the material substrate 104 and / or the surface oxide layer on the surface of the material substrate 104. This material is not sensitive to water, but the sol-gel placed on the material can protect other adjacent structures that may be sensitive to water.

[0090] The second layer 106 is disposed on the second surface 110 of the sol-gel 102, opposite the first surface 108 of the sol-gel 102. The thickness of the sol-gel 102 can be less than the thickness of the material substrate 104. The thickness of the sol-gel 102 can be greater than the thickness of the material substrate 104. The thickness of the sol-gel 102 is about 1 μm to about 10 μm, for example, about 1 μm, about 2 μm, about 3 μm, about 4 μm, about 5 μm, about 6 μm, about 7 μm, about 8 μm, or about 10 μm. Thinner coatings may have fewer defects (more likely to be defect-free), while thicker coatings may provide more wear, electrical, and / or thermal protection for the underlying material substrate 104.

[0091] The second layer 106 includes an organic material (e.g., an organic chemical composition) configured to bond and / or adhere to the sol-gel 102. The second layer 106 includes a paint, a primer, a topcoat, a polymer coating (e.g., an epoxy coating and / or a polyurethane coating), a polymer material, a composite material (e.g., a filled composite material and / or a fiber-reinforced composite material), a laminate, or a mixture thereof. The second layer 106 includes at least one of a polymer, a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a paint, a polyurethane, and a polyester. The second layer 106 may additionally include at least one of a pigment, a binder, a surfactant, a diluent, a solvent, a particle (e.g., a mineral filler), a corrosion inhibitor, and a fiber (e.g., a carbon fiber, an aramid fiber, and / or a glass fiber).

[0092] The third layer 112 is disposed on a proximal surface 114 of the second layer 106 opposite the second surface 110 of the sol-gel 102. The third layer 112 includes an organic material (e.g., an organic chemical composition) configured to bond and / or adhere to the second layer 106. The third layer 112 includes a paint, a primer, a topcoat, a polymer coating (e.g., an epoxy coating and / or a polyurethane coating), a polymer material, a composite material (e.g., a filled composite material and / or a fiber reinforced composite material), a laminate, or a mixture thereof. The third layer 112 includes at least one of a polymer, a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a paint, a polyurethane, and a polyester. The third layer 112 may additionally include at least one of a pigment, an adhesive, a surfactant, a diluent, a solvent, a particle (e.g., a mineral filler), a corrosion inhibitor, and a fiber (e.g., a carbon fiber, an aramid fiber, and / or a glass fiber).

[0093] Sol-gel formation method

[0094] The method for forming the sol-gel of the present disclosure includes mixing the first organosilane and the second organosilane in an organic solvent, such as an anhydrous organic solvent, such as ethanol, and then stirring for about 1 minute to about 1 hour, such as about 10 minutes. Then add an additional solvent (e.g., distilled water) to the organosilane mixture. Add a hydrophobic agent to the mixture in an amount of about 1wt% to about 8wt% of the mixture, and then stir at room temperature for about 1 minute to about 24 hours. Then add an acid catalyst to the mixture and stir for about 1 minute to about 1 hour, such as about 30 minutes, until the pH of the solution becomes about 2 to about 4, such as about 3. Then introduce a corrosion inhibitor and mix for about 1 hour to about 24 hours. The mixture can be deposited on a material substrate. The deposited mixture can be cured at ambient temperature, or can be heated to increase the rate of curing / sol-gel formation, such as curing at about 100°C for about 1 hour to about 12 hours.

[0095] Figure 2A flow chart of a method 200 for forming a sol-gel 102 is shown. Figure 2 As shown, the sol-gel 102 can be formed by mixing 202 one or more sol-gel ingredients. The sol-gel ingredients include two or more of an organosilane, an acid catalyst, a hydrophobic agent, and a corrosion inhibitor. Generally speaking, mixing 202 is performed by combining (e.g., dispersing, emulsifying, suspending, and / or dissolving) the ingredients of the sol-gel formulation in an organic solvent, such as an anhydrous organic solvent or water, and stirring the sol-gel formulation.

[0096] Mixing 202 includes mixing sol-gel components to form a sol-gel mixture (e.g., a solution, mixture, emulsion, suspension and / or colloid). Mixing 202 includes mixing all sol-gel components together at the same time. Optionally, mixing 202 includes mixing any two components (e.g., a first organic silane and a second organic silane in an organic solvent) to form a first mixture, and then mixing the remaining components into the first mixture to form a second mixture. The water content of each of the first mixture and the second mixture is from about 5wt% of water in the mixture to about 15wt% of water in the mixture, such as from about 5wt% to about 12wt%, such as from about 5wt% to about 10wt%, such as from about 5wt% to about 8wt%, such as from about 8wt% to about 10wt%. The ethanol content of each of the first mixture and the second mixture is from about 20wt% of ethanol in the mixture to about 30wt% of water in the mixture, such as from about 21wt% to about 29wt%, such as from about 21wt% to about 25wt%, such as from about 21wt% to about 24wt%, or such as from about 21wt% to about 27wt%.

[0097] Mixing 202 may include dissolving, suspending, emulsifying, and / or dispersing the sol-gel component in an organic solvent prior to mixing with one or more other sol-gel components. Examples of solvents for dissolving, suspending, emulsifying, and / or dispersing the sol-gel component include one or more of alcohols (e.g., ethanol or propanol), ethylene glycol, propylene glycol, polyethylene glycol, polypropylene glycol, ethers (e.g., dimethyl ether or dipropylene glycol dimethyl ether), glycol ethers, tetrahydrofuran (THF), N-methyl-2-pyrrolidone (NMP), and dimethyl sulfoxide (DMSO).

[0098] Additionally or alternatively, mixing 202 can include mixing one or more sol-gel components as solids, polymers, and / or powders with one or more other sol-gel components. For example, when mixing 202 includes mixing solids, powders, and / or viscous liquids, mixing 202 can include mixing using a high shear mixer (e.g., a paint shaker or a planetary centrifugal mixer or agitator). High shear mixers are useful for crushing and / or finely dispersing solids to form a substantially uniform mixture. For example, high shear mixers can dissolve, suspend, emulsify, disperse, homogenize, de-agglomerate, and / or decompose solids into a sol-gel formulation.

[0099] The sol-gel components during mixing 202 may be diluted to control the self-condensation reaction, thereby increasing the shelf life of the mixed sol-gel formulation. Mixing 202 may include forming a mixture (a mixture of first organosilane + second organosilane + acid catalyst) with a concentration ratio of about 0.1:1:0.1 to about 10:1:10 of the first organosilane to the second organosilane to the acid catalyst in the solution. For example, the ratio of the first organosilane, the second organosilane and the acid catalyst may be 2:1:2.

[0100] Mixing 202 may include forming a weight percentage (wt %) of a hydrophobic agent inhibitor in the mixture from about 1 wt % to about 8 wt %, such as from about 2 wt % to about 5 wt %, such as from about 2 wt % to about 4 wt %, such as from about 2 wt % to about 3 wt %. The sol-gel formulation may include a corrosion inhibitor, and mixing 202 includes forming a weight percentage (wt %) of the corrosion inhibitor in the mixture (first organosilane + second organosilane + acid catalyst + hydrophobic agent + corrosion inhibitor to the mixture) from about 0.3 wt % to about 50 wt % to the mixture, such as from about 1 wt % to about 45 wt %, such as from about 2 wt % to about 40 wt %, such as from about 3 wt % to about 35 wt %, such as from about 4 wt % to about 25 wt %, such as from about 8 wt % to about 22 wt %, for example about 10 wt %, about 12 wt %, about 15 wt %.

[0101] During mixing 202, the corrosion inhibitor can cause 90% (D90) of the total particles in the mixture to have a particle diameter of less than about 2 μm to about 5 μm, such as about 2 μm, about 3 μm, about 4 μm, or about 5 μm. Smaller particle sizes can allow the corrosion inhibitor to be uniformly mixed in the mixture. The particle size described herein can refer to the average particle size. The average particle size can be determined in commercially classified products according to various methods, such as ISO 4406, or determined by laser light scattering.

[0102] The sol-gel mixture can be incubated 204 for a period of time, such as from about 1 minute to about 60 minutes, such as from about 5 minutes to about 30 minutes, such as from about 10 minutes to about 20 minutes. The incubation period allows one or more CC double bonds to polymerize to form alkyl chains, thereby increasing the stability of the sol-gel. In addition, the storage period refers to the time period from mixing to forming a sol-gel (for example, the mixture becomes too viscous to be used). The storage period can be from about 1 hour to about 24 hours, such as from about 2 hours to about 8 hours, such as about 4 hours. Incubation 204 can be carried out under ambient conditions (for example, room temperature) and / or at high temperatures. Suitable incubation temperatures include from about 10°C to about 100°C, such as from about 20°C to about 70°C, such as from about 30°C to about 50°C, for example about 40°C. Incubation 204 includes allowing the mixture including the sol-gel component to be placed at room temperature for about 30 minutes or more after mixing the mixture including the sol-gel component.

[0103] The method of the present disclosure includes curing a mixture containing sol-gel components. Figure 2 As shown, curing 206 may include drying a mixture including a sol-gel component placed on a material substrate 104, and may be performed under ambient conditions, at room temperature, and / or at elevated temperatures. The curing temperature is from about 10°C to about 150°C, such as from about 30°C to about 100°C, such as from about 50°C to about 90°C, for example, about 60°C, about 70°C, about 80°C. Curing 308 may be performed for a period of time, such as from about 1 minute to about 48 hours, such as from about 5 minutes to about 24 hours, such as from about 10 minutes to about 8 hours, such as from about 30 minutes to about 4 hours, for example, about 1 hour.

[0104] Curing 206 may include coating the material substrate 104 with the sol-gel mixture and curing the sol-gel mixture. Coating may include wetting the material substrate 104 with the mixture including the sol-gel component, for example, by spraying, dipping, brushing, dipping and / or wiping the mixture including the sol-gel component onto the material substrate 104. For example, suitable spraying forms include spraying with a spray gun, a high-volume low-pressure spray gun and / or a hand pump sprayer. The mixture including the sol-gel component is allowed to drain from the wet material substrate 104 for several minutes (e.g., 1-30 minutes, 1-10 minutes or 3-10 minutes), and, if necessary, excess, un-drained mixture can be sucked off the material substrate 104 and / or gently blown off the material substrate 104 by compressed air.

[0105] The coating includes cleaning and / or pre-treating the material substrate 104 before wetting the material substrate with the mixture containing the sol-gel components. Before applying the sol-gel coating, the metal substrate can be pre-treated by immersing the metal substrate in a solution maintained at a pH between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH. The solution may include about 3 g / L to about 22 g / L of a water-soluble trivalent chromium salt, about 1.5 g / L to about 11.5 g / L of an alkali metal hexafluorosilicate, about 0 g / L (e.g., 0.1 g / L) to about 10 g / L of a water-soluble thickener, and about 0 g / L (e.g., 0.1 g / L) to about 10 g / L of a water-soluble surfactant selected from a nonionic surfactant, an anionic surfactant, a cationic surfactant, and a combination thereof per liter of solution.

[0106] Typically, the sol-gel 102 adheres and / or bonds better to a clean, bare material substrate that is substantially free of dirt, non-reactive surface oxides and / or corrosion products and is preferably filled with a sufficient concentration of reactive hydroxyls or other chemically reactive species. The material substrate surface preparation method may include degreasing, alkaline washing, chemical etching, chemical deoxidation, mechanical deoxidation (e.g., grinding and / or lapping) and / or other suitable methods for creating a sol-gel compatible surface. The coating 206 typically does not include coating the metal substrate 104 with a primer or forming a chemical conversion coating on the metal substrate 104 unless the coating is used to produce a hydroxyl-rich substrate or otherwise improve compatibility with the sol-gel. The material substrate surface can become hydroxyl-rich by depositing a silica hydroxy acid salt on the material surface.

[0107] After coating and / or curing 206, the sol-gel is suitable for exposure to an external environment and / or for application of a second layer 106. The second layer 106 of organic material may be deposited before curing 206 is fully completed, for example, the deposition of the second layer 106 is at least partially simultaneous with curing 206. Deposition may include coating, spraying, dipping, contacting, adhering and / or combining the sol-gel 102 with the organic material to form the second layer 106. The second layer includes a primer, a coating, a fiber reinforced plastic, or other suitable organic material.

[0108] After coating 210, the sol-gel is suitable for exposure to apply the third layer 112. Deposition may include coating, spraying, dipping, contacting, adhering and / or combining the second layer 106 with an organic material to form the third layer 112. The third layer includes paint, fiber reinforced plastic or other suitable organic material.

[0109] Example

[0110] Example 1: A high temperature resistant (HTR) sol-gel coating formulation having a molar ratio of 1:1 between tetraethylorthosilicate (TEOS) and vinyltriethoxysilane (VTS).

[0111] An equimolar mixture of 0.05 mol TEOS and 0.05 mol VTS was added to a reaction flask and stirred for 10 minutes with a magnetic stirrer, as shown in Table 1. 0.3 mol ethanol was added as a solvent and stirred for another 10 minutes. 0.25 mol distilled water was added and stirred vigorously at room temperature for more than 10 minutes. In order to ensure complete hydrolysis, 1 N hydrochloric acid solution was added for acid catalysis. 1 N hydrochloric acid was added until the pH of the solution was 3, for example, 0.1 mol hydrochloric acid was added. The final solution was stirred vigorously for 16 hours at room temperature (RT) to ensure hydrolysis and concentration of the silica network.

[0112] Table 1.

[0113] Chemical name Molecular weight Number of moles Weight / g Tetraethyl orthosilicate (TEOS) 208.3 0.05 10.4 Vinyltriethoxysilane (VTS) 190.3 0.05 9.5 Ethanol 46 0.3 13.8 water 18 0.25 4.5 1N hydrochloric acid (catalyst) 36.45 0.1 0.1

[0114] The sol-gel solution was applied on clean Al 2024 substrate by dip coating and cured at room temperature. No discoloration was observed after exposure at 250°C for 100 hours. The transparency of the prepared sol-gel coating was found to be 90% with no haze or haze less than 5% according to visual inspection. After exposure at 250°C for 100 hours, the water contact angle decreased from 62.1° to 56.6°, indicating that the coating was not hydrophobic, as shown in Figure 2. Figure 3A and Figure 3B As shown. Through optical microscopy and scanning electron microscopy (SEM) observation, after exposure to 250 ° C for 100 hours, the sol-gel showed cracking, as shown in FIG. 4A to FIG. 4D The results show that the strength and corrosion inhibition are reduced. The cured coating was analyzed by Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). FTIR data showed that the -1 and 770cm -1 The peaks are Si-O-Si connections and silica networks, respectively. Figure 5 TGA analysis showed that the weight loss between 30°C and 200°C was 2.5 wt%, indicating that the solvent evaporated, and the weight loss between 200°C and 520°C was 4.5 wt%, indicating that the organic residue evaporated, as shown in Figure 6 shown.

[0115] Example 2: High temperature resistant (HTR) sol-gel coating formulations with different molar ratios of TEOS to VTS.

[0116] Three mixtures were prepared. The first mixture had a molar ratio of TEOS to VTS of 1.5:1. The second mixture had a molar ratio of TEOS to VTS of 2:1. The third mixture had a molar ratio of TEOS to VTS of 2.5:1. Each mixture was added separately to a reaction flask and stirred with a magnetic stirrer for 10 minutes, as shown in Table 2. 0.3 mol of ethanol was added as a solvent and stirred for another 10 minutes. 0.25 mol of distilled water was added and stirred vigorously at room temperature for more than 10 minutes. To ensure complete hydrolysis, 1N hydrochloric acid solution was added for acid-catalyzed reaction. 1N hydrochloric acid was added until the pH of the solution was 3, for example, 0.1 mol of hydrochloric acid was added. The final solution was stirred vigorously for 16 hours at room temperature (RT) to ensure hydrolysis and concentration of the silica network.

[0117] Table 2.

[0118] Chemical name Mixture 1 Mixture 2 Mixture 3 Tetraethyl orthosilicate (TEOS) 0.75 0.1 0.125 Vinyltriethoxysilane (VTS) 0.05 0.05 0.05 Ethanol 0.3 0.3 0.3 water 0.25 0.25 0.25 1N hydrochloric acid (catalyst) 0.1 0.1 0.1

[0119] The sol-gel solution was applied on clean Al 2024 substrate by dip coating and cured at room temperature. No discoloration was observed after exposure at 250°C for 100 hours. The transparency of the prepared sol-gel coating was found to be 90% with no haze or haze less than 5% by visual inspection. No cracking was observed in any of the mixtures after exposure at 250°C for 100 hours using SEM, as shown in Figure 2. FIG. 7A to FIG. 7C shown.

[0120] After heating mixture 2 at 250℃ for 100 hours, the polarization resistance (Rp) decreased and the corrosion current (i corr ) increases, as shown in Table 3 and Figure 8 This indicates that even if cracks that reduce the structural integrity are not formed, the corrosion resistance will be reduced after heating due to the hydrophobicity of the sol-gel. The cured coatings were analyzed by Fourier transform infrared spectroscopy (FTIR), where the 1030 cm -1 The peak corresponds to Si-O-Si bond, 765 cm -1 The peaks correspond to the silica network, e.g. Fig. 9 shown.

[0121] Table 3.

[0122] sample <![CDATA[Current density (i corr ) A]]> Polarization resistance (Rp)Ω Mixture 2 <![CDATA[2.214×10 -9 ]]> <![CDATA[1753×10 4 ]]> Heated mixture 2 <![CDATA[4.238×10 -8 ]]> <![CDATA[1123×10 3 ]]>

[0123] After heating mixture 2 at 250 °C for 100 h, the water contact angle decreased from 78.5° to 44.2°, indicating that the coating became hydrophobic after heating, as shown in Figure 2. Fig. 10A and Fig. 10B As shown in Figure 1, after heating mixture 1 at 250°C for 100 hours, the polarization resistance (Rp) decreased and the corrosion current (i corr ) increases, as shown in Table 4 and Fig.11This indicates that the corrosion resistance decreases and the hydrophobicity increases after heating, even though no cracks are formed that would reduce the structural integrity.

[0124] Table 4.

[0125] sample <![CDATA[Current density (i corr ) A]]> Polarization resistance (Rp)Ω Mixture 2 <![CDATA[2.334×10 -9 ]]> <![CDATA[1779×10 4 ]]> Heated mixture 2 <![CDATA[4.478×10 -8 ]]> <![CDATA[1002×10 3 ]]>

[0126] Example 3: High temperature resistant (HTR) sol-gel coating formulation with a 2:1 molar ratio of TEOS to VTS and a hydrophobic agent.

[0127] A mixture of 0.1 mol TEOS and 0.05 mol VTS was added to a reaction bottle and stirred for 10 minutes with a magnetic stirrer, as shown in Table 5. 0.3 mol ethanol was added as a solvent and stirred for another 10 minutes. 0.25 mol distilled water was added and stirred vigorously at room temperature for 10 minutes. In order to ensure complete hydrolysis, 1N hydrochloric acid solution was added for acid-catalyzed reaction. 1N hydrochloric acid was added until the pH of the solution was 3, for example, 0.1 mol hydrochloric acid was added. With stirring, hydrophobic agent perfluorooctyl triethoxysilane (PFOTES) was added dropwise to a final concentration of 2 wt % of PFOTES in the total mixture. The final solution was stirred vigorously for 16 hours at room temperature (RT) to ensure hydrolysis and concentration of the silica network.

[0128] Table 5.

[0129]

[0130]

[0131] The sol-gel solution was applied on clean Al 2024 substrate by dip coating and cured at room temperature. No discoloration was observed after exposure at 250°C for 100 hours. The transparency of the prepared sol-gel coating was found to be 90% with no haze or haze less than 5% by visual inspection. No cracking was observed in any of the mixtures after exposure at 250°C for 100 hours using SEM, as shown in Figure 2. Fig. 12A and Fig. 12B shown.

[0132] After heating at 250 °C for 100 h, the water contact angle increased from 105.2° to 110.8°, indicating that the coating became more hydrophobic after heating, as shown in Figure 2. Fig.13A and Fig. 13B After heating at 250℃ for 100 hours, the polarization resistance (Rp) increases and the corrosion current (i corr ) is reduced, as shown in Table 6 and Fig.14 This indicates corrosion resistance after heating, which can be attributed to the increase in hydrophobicity and the prevention of sol-gel cracking. The cured coatings were analyzed by Fourier transform infrared spectroscopy (FTIR), where 1054 cm-1 The peak corresponds to Si-O-Si bond, 967 cm -1 Peak corresponds to COC bond, 780cm -1 The peaks correspond to Si-OC and silica networks, such as Fig.15 shown.

[0133] Table 6.

[0134] sample <![CDATA[Current density (i corr ) A]]> Polarization resistance (Rp)Ω Before heating <![CDATA[4.275×10 -8 ]]> <![CDATA[4715×10 3 ]]> After heating <![CDATA[9.165×10 -10 ]]> <![CDATA[3696×10 4 ]]>

[0135] The pencil hardness test according to ASTM D 3363 shows that the hardness is 4H after immersion in water for 336 hours.

[0136] Example 4: High temperature resistant (HTR) sol-gel coating formulation with 2:1 TEOS and VTS molar ratio and hydrophobic agent and cross-linking agent.

[0137] A mixture of 0.1 mol TEOS, 0.05 mol VTS and 0.1 mol methyltrimethoxysilane (MTMS) was added to a reaction bottle and stirred for 10 minutes with a magnetic stirrer, as shown in Table 7. The role of MTMS is to increase the amount of crosslinking, thereby improving hydrophobicity and / or strength. 0.3 mol ethanol was added as a solvent and stirred for another 10 minutes. 0.25 mol distilled water was added and stirred vigorously at room temperature for 10 minutes. In order to ensure complete hydrolysis, 1N hydrochloric acid solution was added for acid-catalyzed reaction. 1N hydrochloric acid was added until the pH of the solution was 3, for example, 0.1 mol hydrochloric acid was added. With stirring, hydrophobic agent perfluorooctyl triethyloxysilane (PFOTES) was added dropwise to a final concentration of 2 wt % of PFOTES in the total mixture. The final solution was stirred vigorously for 16 hours at room temperature (RT) to ensure hydrolysis and concentration of the silica network.

[0138] Table 7.

[0139]

[0140]

[0141] The sol-gel solution was applied on clean Al 2024 substrate by dip coating and cured at room temperature. No discoloration was observed after exposure at 250°C for 100 hours. The transparency of the prepared sol-gel coating was found to be 90% with no haze or haze less than 5% by visual inspection. No cracking was observed in any of the mixtures after exposure at 250°C for 100 hours using SEM. The cured coatings were analyzed by Fourier transform infrared spectroscopy (FTIR) where 1038 cm -1 The peak corresponds to Si-O-Si bond, 1271 cm -1 The peak corresponds to the ether C-O-C bond, 771 cm-1 The peaks correspond to Si-OC and silica networks, such as Fig.16 shown.

[0142] ASTM B117 salt spray test results after 24 hours produced no blistering or adhesion complications. Salt spray test results after 336 hours of exposure to 5% sodium chloride solution produced minimal blistering and / or pitting.

[0143] Additional aspects

[0144] E1. A sol-gel mixture comprising a first organosilane having a structure represented by Formula V: Each R 10 , R 11 and R 12 Independently linear or branched C 1-20 Alkyl, R 9 A second organosilane selected from alkyl, cycloalkyl, ether, epoxide and aryl, represented by formula (I), wherein the second organosilane is different from the first organosilane, and a hydrophobic agent, whose concentration in the sol-gel mixture is about 1 wt % to about 8 wt % of the total sol-gel mixture.

[0145] E2. The sol-gel mixture of embodiment E1, wherein the first organosilane and the second organosilane have a molar ratio of the first organosilane to the second organosilane in the sol-gel mixture of about 0.1:1 to about 10:1.

[0146] E3. The sol-gel mixture of embodiment E1 or E2, wherein the first organosilane is present in the sol-gel mixture at about 0.01 mol to about 1.0 mol.

[0147] E4. The sol-gel mixture of any one of embodiments E1-E3, wherein the second organosilane is present in the sol-gel mixture at a concentration of about 0.01 mol to about 1.0 mol.

[0148] E5. The sol-gel mixture of any one of embodiments E1 to E4, wherein the first organosilane is selected from tetraethylorthosilicate, vinyltriethoxysilane, or methyltrimethoxysilane.

[0149] E6. The sol-gel mixture of embodiment E5, wherein the second organosilane is selected from tetraethylorthosilicate, vinyltriethoxysilane, or methyltrimethoxysilane, and the second organosilane is different from the first organosilane.

[0150] E7. The sol-gel mixture of any one of embodiments E1 to E6, wherein the hydrophobic agent comprises a fluoride group.

[0151] E8. The sol-gel mixture of any one of embodiments E1-E7, wherein the hydrophobic agent comprises perfluorooctyltriethoxysilane.

[0152] E9. The sol-gel mixture of any one of embodiments E1 to E8, wherein the hydrophobic agent comprises a concentration of about 2 wt % to about 3 wt % of the total sol-gel mixture.

[0153] E10. The sol-gel mixture of any one of embodiments E1 to E9, wherein the sol-gel further comprises a corrosion inhibitor.

[0154] E11. The sol-gel mixture of embodiment E10, wherein the corrosion inhibitor is mercaptothiadiazole.

[0155] E12. The sol-gel mixture of embodiment E11, wherein the dimercaptothiadiazole is 2,5-dimercapto-1,3,4-thiadiazole.

[0156] E13. A crosslinked siloxane sol-gel comprising a first siloxane unit represented by formula (I): Where X is oxygen, R 1 is hydrogen, oxygen, hydroxyl or silane group, R 2 is a hydrogen, hydroxyl or silane group, each R 3 and R 4 Independently linear or branched C 1-20 Alkyl, C 1-20 Cycloalkyl, oxysilane, ether, epoxide, arylalkyl fluoride, cycloalkyl fluoride and aryl fluoride groups, n is 1 to 100, a second siloxane unit represented by formula (I), wherein the second organosilane is different from the first organosilane, and a hydrophobic agent represented by formula (I), wherein the hydrophobic agent includes at least one alkyl fluoride group.

[0157] E14. The sol-gel of embodiment E13, wherein the first siloxane units and the second siloxane units have a molar ratio of the first siloxane units to the second siloxane units in the sol-gel of about 0.1:1 to about 10:1.

[0158] E15. The sol-gel of any one of embodiments E13 or E14, wherein for the first siloxane unit, R 1 is hydroxyl, R 2 Does not exist, R 3 is oxysilane, and R 4 It is oxysilane.

[0159] E16. The sol-gel of any one of embodiments E13 to E15, wherein for the second siloxane unit, R 1 is oxygen, R 2 Does not exist, R3 is oxysilane, and R 4 It is a C2 olefin.

[0160] E17. The sol-gel of any one of embodiments E13 to E16, wherein for the hydrophobic agent, R 1 is oxygen, R 2 Does not exist, R 3 is oxysilane, and R 4 It is a C9 alkyl fluoride.

[0161] E18. The sol-gel of any one of embodiments E13-E17, wherein the sol-gel further comprises a corrosion inhibitor.

[0162] E19. The sol-gel of any one of embodiments E13-E18, wherein the sol-gel is represented by formula III: Where X 1 , X 2 and X 3 Including oxygen, R 1 is hydrogen, oxygen, hydroxyl or silane group, R 2 is hydrogen, hydroxyl or silane group, each R 3 , R 4 , R 5 , R 6 , R 7 and R 8 is independently a linear or branched C 1-20 Alkyl, C 1-20 Cycloalkyl, oxysilane, ether, epoxide, aralkyl fluoride, cycloalkyl fluoride and aryl fluoride groups, n is 1 to 100, m is 1 to 100, and p is 1 to 100.

[0163] E20. The sol-gel of embodiment E19, wherein the sol-gel is a polymerized sol-gel having R of the first siloxane unit represented by Formula III 3 , R 4 , R 5 , R 6 , R 7 or R 8 and R of the second siloxane unit represented by Formula III 3 , R 4 , R 5 , R 6 , R 7 or R 8 At least one of cross-linking.

[0164] E21. A method for preparing a sol-gel from a sol-gel mixture, the method comprising making a sol-gel mixture by mixing a first organic silane with a second organic silane in an organic solvent; adding a hydrophobic agent to the sol-gel mixture; and curing the sol-gel mixture to form a sol-gel.

[0165] E22. The method of embodiment E21, wherein the first organosilane and the second organosilane are present in the sol-gel mixture in a molar ratio of first organosilane to second organosilane of about 0.1:1 to about 10:1.

[0166] E23. The method of embodiment E21 or E22, wherein the first organosilane is present in the sol-gel mixture at about 0.01 mol to about 1.0 mol.

[0167] E24. The method of any of embodiments E21-E23, wherein the second organosilane is present in the sol-gel mixture at about 0.01 mol to about 1.0 mol.

[0168] E25. The method of any of embodiments E21-E24, wherein the first organosilane is selected from tetraethylorthosilicate, vinyltriethoxysilane, or methyltrimethoxysilane.

[0169] E26. The method of embodiment E25, wherein the second organosilane is selected from tetraethylorthosilicate, vinyltriethoxysilane, or methyltrimethoxysilane, and the second organosilane is different from the first organosilane.

[0170] E27. The method of any one of embodiments E21-E26, wherein the hydrophobic agent comprises a fluoride group.

[0171] E28. The method of embodiment E27, wherein the hydrophobic agent comprises perfluorooctyltriethoxysilane.

[0172] E29. The method of any one of embodiments E21-E28, wherein the hydrophobic agent is present at a concentration of about 2 wt % to about 3 wt % of the total sol-gel

[0173] E30. The method of any one of embodiments E21-E29, wherein the sol-gel further comprises a corrosion inhibitor.

[0174] E31. The method of embodiment E30, wherein the corrosion inhibitor is mercaptothiadiazole.

[0175] E32. The method of embodiment E31, wherein the dimercaptothiadiazole is 2,5-dimercapto-1,3,4-thiadiazole.

[0176] In general, the sol-gel of the present disclosure provides a high temperature resistant sol-gel capable of withstanding temperatures up to 450°F while maintaining corrosion resistance and aesthetics. The sol-gel coating remains transparent at high temperatures with little cracking or fading. The sol-gel is substantially uniform, has limited and / or no metal oxides, which reduces cracking and fading while maintaining hydrophobicity to extend the useful life of the sol-gel. The sol-gel reduces and / or eliminates the need for chromates and reduces the production cost, maintenance cost, and repair cost of sol-gel applications. The sol-gel of the present disclosure is substantially free of metal oxides, such as metal alkoxides, which reduces the total amount of cracking and deformation formed due to heating the sol-gel.

[0177] Although we have described preferred aspects, those of ordinary skill in the art will readily recognize that substitutions, changes, and modifications may be made without departing from the inventive concept. Therefore, on the basis of this description, the claims are to be interpreted broadly, with the support of the full range of equivalents known to those of ordinary skill in the art. The embodiments illustrate the disclosure but are not intended to limit it. Therefore, the disclosure is defined by the claims and only limited where necessary relative to the relevant prior art.

Claims

1. A sol-gel mixture comprising: A first organosilane having a structure represented by Formula V: Among them: Each R 10 , R 11 and R 12 Independently linear or branched C 1-20 Alkyl, and R 9 is selected from alkyl, cycloalkyl, ether, epoxide and aryl, a second organosilane represented by formula (I), wherein the second organosilane is different from the first organosilane, and A hydrophobic agent, wherein the concentration of the hydrophobic agent in the sol-gel mixture is about 1 wt % to about 8 wt % of the total amount of the sol-gel mixture. 2 . The sol-gel mixture of claim 1 , wherein the first organosilane and the second organosilane have a molar ratio of the first organosilane to the second organosilane in the sol-gel mixture of about 0.1:1 to about 10:

1.

3. The sol-gel mixture according to claim 1, wherein the first organosilane is selected from tetraethylorthosilicate, vinyltriethoxysilane or methyltrimethoxysilane.

4. The sol-gel mixture according to claim 3, wherein the second organosilane is selected from tetraethylorthosilicate, vinyltriethoxysilane or methyltrimethoxysilane, and the second organosilane is different from the first organosilane.

5. The sol-gel mixture of claim 1, wherein the hydrophobic agent comprises a fluoride group.

6. The sol-gel mixture of claim 1, wherein the hydrophobic agent has a concentration of about 2 wt% to about 3 wt% of the total sol-gel.

7. A cross-linked silicone sol-gel (102), comprising The first siloxane unit represented by formula (I): Where X is oxygen, R 1 is a hydrogen, oxygen, hydroxyl or silane group, R 2 is a hydrogen, hydroxyl or silane group, Each R 3 and R 4 Independently linear or branched C 1-20 Alkyl, C 1-20 Cycloalkyl, silane oxide, ether, epoxide, arylalkyl fluoride, cycloalkyl fluoride and aryl fluoride groups, and n is 1 to 100; a second siloxane unit represented by formula (I), wherein the second siloxane unit is different from the first siloxane unit; and A hydrophobic agent represented by formula (I), wherein the hydrophobic agent includes at least one alkyl fluoride group.

8. The sol-gel (102) according to claim 7, wherein the first siloxane unit and the second siloxane unit have a molar ratio of the first siloxane unit to the second siloxane unit of about 0.1:1 to about 10:1 in the sol-gel.

9. The sol-gel (102) according to claim 7, wherein for the first siloxane unit, R 1 is hydroxyl, R 2 Does not exist, R 3 is oxysilane, and R 4 It is oxysilane.

10. The sol-gel (102) according to claim 7, wherein for the second siloxane unit, R 1 is oxygen, R 2 Does not exist, R 3 is oxysilane, and R 4 It is a C2 olefin.

11. The sol-gel (102) according to claim 7, wherein for the hydrophobic agent, R 1 is oxygen, R 2 Does not exist, R 3 is oxysilane, and R 4 It is a C9 alkyl fluoride.

12. The sol-gel (102) according to claim 7, wherein the sol-gel (102) further comprises a corrosion inhibitor.

13. The sol-gel (102) according to claim 7, wherein the sol-gel (102) is represented by Formula III: Where X 1 , X 2 and X 3 Including oxygen, R 1 is hydrogen, oxygen, hydroxyl or silane group, R 2 is hydrogen, hydroxyl or silane group, Each R 3 , R 4 , R 5 , R 6 , R 7 and R 8 is independently a linear or branched C 1-20 Alkyl, C 1-20 Cycloalkyl, silane oxide, ether, epoxide, arylalkyl fluoride, cycloalkyl fluoride and aryl fluoride groups, n is 1 to 100, m is 1 to 100, and p is 1 to 100.

14. The sol-gel (102) according to claim 13, wherein the sol-gel (102) is a polymerized sol-gel having R of the first siloxane unit represented by formula III 3 , R 4 , R 5 , R 6 , R 7 or R 8 and R of the second siloxane unit represented by formula III 3 , R 4 , R 5 , R 6 , R 7 or R 8 At least one of cross-linking.

15. A method for preparing a sol-gel (102) from a sol-gel mixture, the method comprising: making a sol-gel mixture by mixing a first organosilane with a second organosilane in an organic solvent; adding a hydrophobic agent to the sol-gel mixture; and The sol-gel mixture is cured to form a sol-gel.

16. The method of claim 15, wherein the first organosilane and the second organosilane are present in the sol-gel mixture in a molar ratio of first organosilane to second organosilane of about 0.1:1 to about 10:

1.

17. The method of claim 15, wherein the first organosilane is selected from tetraethylorthosilicate, vinyltriethoxysilane, or methyltrimethoxysilane.

18. The method of claim 17, wherein the second organosilane is selected from tetraethylorthosilicate, vinyltriethoxysilane, or methyltrimethoxysilane, and the second organosilane is different from the first organosilane.

19. The method of claim 15, wherein the hydrophobic agent is present in the sol-gel mixture at a concentration of about 2 wt% to about 3 wt% of the total sol-gel.

20. The method of claim 15, wherein the sol-gel (102) further comprises a corrosion inhibitor.